Pojetí tacitních znalostí v paradigmatu sjednoceného pole. / The concept of tacit knowledge in the paradigm of a unified field - Radim Šíp; Vlastimil Švec (Czech Pedagogical Society, 2013)
The aim of this theoretical study is to clear the concept of tacit knowledge. In the first part of the text, the authors show where the confusion comes from. If we take knowledge as a mental representation we will not, in fact, be able to inquire it. In the second part, an alternative, which has been alive for more than a hundred years, isdetected in works on knowledge and knowing by scholars such as Dewey and Piaget. Then, in the third part, the authors depict the hesitation of specialists that could not abandon the old traditional understanding of knowledge (in the study connected with the "paradigm of separated objects") and their need to across it. Thus they staybetween the old and the new paradigm (the new one is in the text referred to as the "paradigm of aunified field") and therefore, their theories are very often confusing and unusable in praxis. For better understanding of the two - traditional and alternative - paradigms, the authors offer ashort introduction to both in the fourth and fifth parts. The study ends by the conclusion that if we are able to understand knowledge not as a representation, but as a dynamic structure of aunified field, we will be able to grasp tacit knowledge as atacit dimension of the structure and thus we will be able to studyit more properly.